Can the Gap between Food Wastage and Starvatıon be Brıdged ın Indıa? - Muskan Gupta (International Journal of Advanced Science and Technology, 2020)
Our world produces more than sufficient food to serve the current world population and yet there are over 850 millions of people starving in the world. The people never consume one third of the food produced by the world. In India, on one hand, over 2.5 million of people die, every year, due to hunger, and on the other hand, fifty thousand crore rupees worth of quantitative food are being wasted in India every year. World’s 2nd largest producer of food is none but India. Yet, over 194 million people are malnourished in India. Every night, more than 20 crores of Indians sleep with empty stomach but 7000 of them never wake up. Isn’t it ironical? It not only impacts millions of unfortunate lives but also affects our economy to a significant extent! Despite the issue being so critical, it has not able to catch the deserved attention of government or private organizations.Present study analyzes the data gathered from various NGOs and organizations working towards mitigating the gap between food wastage and starvation, in India. This is an attempt to quantify how food wastage can be managed in India. The data collected through secondary research will be analyzed using appropriate statistical tools. Results of this study will help government bodies, institutions and private organizations to not only spot the gaps but also come up with various innovative Food Waste Management models to solve the social and economic crisis.